Assuming angle F is 68°, angle H will be
.. 360° -2*102° -68° = 88° . . . . . . . . selection B
Hey! :)
you went on the roller coaster 7 times and the ferris wheel 5 times
Hope this helps! :)
Step-by-step explanation:
Applying rules of exponents to solve the given problems;
4^3 x 4^5 =
5^8 ÷ 5^-2 =
(6^3 ) ^ 4 =
For these problems, the applicable rules of exponents are;
aᵇ x aⁿ = aᵇ⁺ⁿ
aᵇ ÷ aⁿ = aᵇ⁻ⁿ
(aᵇ)ˣ = aᵇˣ
For the first problem; 4³ x 4⁵
aᵇ x aⁿ = aᵇ⁺ⁿ
4³ x 4⁵ = 4³⁺⁵ = 4⁸
Second problem: aᵇ ÷ aⁿ = aᵇ⁻ⁿ
5⁸ ÷ 5⁻² = 5⁸⁻⁽⁻²⁾ = 5⁸⁺² = 5¹⁰
Third problem; (aᵇ)ˣ = aᵇˣ
(6³)⁴ = 6³ˣ⁴ = 6¹²
Answer:
1) incorrect
2) incorrect
Step-by-step explanation:
-2x-2x = 0 ?
-2x -2x = -4x
It will be 0 only if x = 0.
Not always true, so incorrect
x+x = x² ?
2x = x²
They will be equal if x = 0 or 2.
Not always true so incorrect
Answer:
Acute
Step-by-step explanation:
An acute triangle has three angles that each measure less than 90 degrees.